THE ROLE OF FATHER’S PARENTING STYLE CHILDREN AGED 24–60 MONTHS - Astrid Primadani; Dina Sulviana Damayanti; Putri Malika Prastiari (Jurnal Smart Kebidanan, 2024)
The quality of a father's knowledge about parenting is still low (27.9%), and the absence of a father can hinder a child's development, which may affect their adulthood. The absence of a father can hinder a child's development from infancy through childhood and into adulthood. Children are the buds, potential, and next generation of the nation's ideals. Children have a strategic role in ensuring the existence of the nation and state in the future. This study aims to determine the involvement of the father's role in the care of children aged 24-60 months in Bekasi City, West Java in 2023. This research is included in the type of descriptive research.  The number of respondents used in this study are 40 respondents. The technique used in this study was accidental sampling. Data processing in this study used excel software. Father respondents in this study seen from the results answered by respondents, showed that fathers play a role in childcare. The role of the father in this research shows that the father plays a role as a provider or as a facilitator and protector in the family, the role of child specialist and educator is also visible in the father because he participates in caring for the child. Decision maker, building responsive communication, and being a nurturing mother is seen in the role of father in the family